The Ancestry of the Australian Prime Ministership: "the blue ribbon of the highest possible ambition". (March 2015) - Strangio, Paul
Abstract : More than a century after the birth of the Commonwealth of Australia, the office of prime minister is the apex of the nation's political life. Yet little has been written about the antecedence and evolution of the office of prime minister. This article takes a step towards redressing this neglect by considering how the Westminster‐derived model of the prime ministership was conditioned by the nature and form of executive office in the Australian colonies in the second half of the nineteenth century. The experience of the colonial legislatures predisposed against fears of an overweening executive. The constitutional Conventions of the 1890s were dominated by seasoned colonial politicians with benign attitudes towards executive authority. Yet as delegates grappled with the challenge of marrying responsible government to a federal system, the form of executive was debated rather than treated as fait accompli . These deliberations hinted at their expectations for the prime ministership in a federated Australia: the office would be the most powerful and greatest political prize in the new nation. The article concludes by suggesting that the first Commonwealth decade was a transitional period for the prime ministership (with pre‐Federation patterns still evident) and identifying the Fisher Government of 1910–13 as heralding a shift to a more modern form of (party‐based) executive governance.